Beyond the Textbook: The Importance of Common Sense in the EFL Classroom - Zainol Hasan; Risma Fahrul Amin (Hikamatzu | Journal of Multidisciplinary, 2025)
This study explores the pivotal role of common sense in English Language Teaching (ELT), particularly in addressing the limitations of textbook-based instruction. While textbooks offer a structured foundation, they often lack the adaptability needed to meet the diverse needs, interests, and learning styles of students. Using a systematic and thematic literature review, this research examines how teachers’ practical judgment—rooted in experience, intuition, and contextual awareness—enhances lesson planning, classroom management, instructional strategies, and assessment. Findings reveal that common sense allows teachers to personalize learning, respond flexibly to challenges, and foster inclusive and dynamic classroom environments. Real-world case studies further demonstrate how teachers apply common sense to support student engagement, autonomy, creativity, and resilience. However, the study also acknowledges that common sense is inherently subjective and must be balanced with sound pedagogical principles. The research calls for the integration of common sense into teacher education and professional development as a vital pedagogical resource, emphasizing reflective practice and teacher agency. Ultimately, effective ELT requires not only theoretical knowledge but also the wisdom to apply it meaningfully in diverse classroom contexts.